Penyuluhan Kesehatan Tentang Pijat Bayi Menggunakan Aromaterapi Essential Oil Bunga Kenanga Terhadap Kualitas Tidur Bayi 6-12 Bulan di Kelurahan Sei Renggas - Mahyunidar; Anggriani, Ririn; Ratnasari, Fika; Wulandari, Hardini (Cattleya Darmaya Fortuna, 2022)
In Indonesia, 44.2% of children have difficulty sleeping, but 72% of parents consider this a minor problem. On the other hand, sleep disorders can affect the baby's growth, make the immune system vulnerable, and disrupt the regulation of the endocrine system. To improve sleep quality and optimize children's growth and development, baby massage could be one solution. The increase in sleep quality or sleep duration in babies who receive baby massage is caused by increasing levels of serotonin which is the main neurotransmitter involved in establishing sleep and suppressing other brain functions. The Sukwati study showed that 73% of babies experienced improved sleep quality after massage. Therefore, experts recommend that baby massage be carried out by mothers and fathers, not massage therapists.